Dissociation of polymeric micelle under hemodynamic shearing. (August 2022) - Zhang, Hao; He, Zhenyu; Fu, Chaopeng; Pan, Pan; Zhu, Yifeng; Xu, Meng; Deng, Shengwei; Ying, Guoqing; Shen, Youqing
Abstract: Many studies have observed the unexpected micelle dissociation occurred upon i.v. injection. However the dynamics and mechanism of in vivo micelle dissociation are still unclear, mainly due to the lack of physiologically representative models. Here, we used microfluidic channels to mimic geometries of vascular networks and related hemodynamic shearing conditions, adopted fluorescence resonance energy transfer (FRET) imaging to monitor the dynamics of the micelle dissociation and applied the dissipative particle dynamics (DPD) to simulate the morphological evolution of micelles under shearing. In vessel-mimicking microfluidic models, we observed the fast dissociation of clinically relevant polyethylene glycol-block-poly(ε-caprolactone) (PEG-PCL) and PEG-block-poly(D, L-lactide) (PEG-PDLLA) micelles that were stable under static conditions. FRET imaging from a pair of fluorophores (Cy5 and Cy5.5) conjugated in the micelle core revealed that the dynamics of micelle dissociation was associated with hemodynamic shearing, which was altered by either tuning the flow rate of mouse blood or changing the geometry of the microchannel. In addition to blood proteins that were generally considered as the major contributors to the micelle dissociation, we found in blood flow, the presence of shear field on particles, as surrogates to red blood cells, significantly influenced the micelle dissociation. Moreover, the DPD stimulation revealed that the morphological evolution of micelles under shearing resulted in the disintegrity of the protective PEG shell, leading to the increased exposure of the hydrophobic core to the outer media, dramatically facilitating the nearby blood components to interact with the inner core and therefore quickly destructed the micellar structures. These findings suggested the mechanism of the shear-induced micelle dissociation in blood flow, which can be directional for the design of micellar nanomedicine with expected circulation lifespan, and therefore high therapeutic efficacy. Graphical Abstract: ga1 Highlights: TThe hemodynamic dissociation of polymeric micelle has been studied in vessel-mimicking microfluidic channels. FRET imaging revealed the dynamics of micelle dissociation was associated with hemodynamic shearing and blood components. DPD simulation suggested that micelles deformed under applied shearing, leading to the fast destruction of micelles.